Avian sperm increase in vitro the release of exosomes from SST-enriched organoids. Issue 4 (April 2021) - Cordeiro, Luiz; Riou, Cindy; Uzbekov, Rustem; Gérard, Nadine
Abstract : In birds, oviductal cells play a crucial role in the storage of sperm via cell-to-cell communication including extracellular vesicles (EV). We developed a culture of oviductal organoids enriched in sperm storage tubules (SSTorg) to demonstrate the release of EV. SSTorg were cultured for 24 h and added to live (LV), frozen (FZ) and lysed (LY) avian sperm, seminal plasma (SP), avian sperm conditioned medium (CM), or bovine sperm (BV). Western blot demonstrated that SSTorg contained EV protein markers, valosin-containing protein (VCP), heat shock proteins (HSP90AA1, HSPA8), and annexins (ANXA2, A4, A5). Co-culture with LV significantly decreased the intracellular level of all these proteins except HSPA8. Immunohistochemistry confirmed this result for VCP and ANXA4. LY, CM, SP and BV had no effect on the intracellular level of these proteins, whereas FZ induced a decrease in ANXA2, A4 and A5. In culture media, VCP and HSP90AA1 signals were detected in the presence of LV, FZ, BV, LY, CM and SP, but no ANXA4 signal was observed in the presence of FZ and SP. ANXA2 and A5 were only detected in the presence of LV. The most abundant EV were less than 150 nm in diameter. ANXA4 and A5 were more abundant in EV isolated from the SSTorg culture medium. This study provides a useful culture system for studying interactions between SST cells and sperm. We demonstrated the release of EV by SSTorg in vitro, and its regulation by sperm. This may be of crucial importance for sperm during storage in hens.